Reliability analysis based on weibull distribution and failure mode effect and criticality anaysis - Suhaireza, Md Esa
In manufacturing industry breakdown due to machine failure affect the product quality, customer satisfaction and product performance. However it is important more over difficult to control and decreasing failure due to unplanned failure. This situation gives a big impact since it leads to product defect, decreasing of performance and increasing of maintenance cost. One of the strategies is using the reliability analysis as the medium to develop a proper maintenance. This reliability analysis identified the characteristics of the failure and the reliability of the machine. For this research two method of reliability analysis used are Weibull distribution and failure mode effect and criticality analysis. For Weibull distribution the quantitative data of the time to failure is applied. Time to failure data is the range of time from the first failure to the next failure to happen. Where in failure mode effect and criticality analysis the data used are the failure mode, failure cause and effects and its probability. These data based on failure data provided from three critical machines on the Camshaft line of automotive manufacturing industry in Malaysia. For this reliability analysis, Weibull distribution analysis ends up the results with the state of characteristics and behaviour of the machine failure. State of the failure characteristics are able to use as the guideline for future analysis of proper maintenance development. Moreover, the value of parameter on the characteristics and behaviour of the failure state leads to estimation of mean time to failure. Meanwhile, from the failure mode and failure cause and effects results leads to identification, classification and clarification of the failure mode and its criticality ranks. In the criticality matrix the degree of seriousness for the critical failure mode is more clearly viable. The criticality matrix leads to decision of corrective action taken with the consideration of safety factor and occurrence of failure. Therefore, the combination of reliability analysis and failure mode and failure cause and effects on machine failure presents more clear and specifics results.